Depreciation: Accounting, Taxes and Business Decisions. - Sterling, Robert R.; Powell, Ray M. (The Accounting Review, 1970)
Reviews the book "Depreciation: Accounting, Taxes and Business Decisions," by J.D. Coughlan and W.K. Strand.